Compound heterozygosity in sodium channel Nav1.7 in a family with hereditary erythermalgia - Lynch Mary E; te Morsche Rene HM; Samuels Mark E; Drenth Joost PH (SAGE Publishing, 2008)
Abstract Hereditary erythermalgia is a painful and debilitating genetic disorder associated with mutations in voltage-gated sodium channel Nav1.7. We have previously reported a Canadian family segregating erythermalgia consistently with a dominant genetic etiology. Molecular analysis of the proband from the family detected two different missense mutations in Nav1.7. In the present study we have performed a long-term follow-up clinical study of disease progression in three affected family members. A more extensive molecular study has also been completed, analyzing the segregation of the two missense variants in the family. The two variants (P610T, L858F) segregate independently with respect to clinical presentation. Detailed genotype/phenotype correlation suggests that one of the two variants (L858F) is causal for erythermalgia. The second variant (P610T) may modify the phenotype in the proband. This is the second reported study of potential compound heterozygosity for coding polymorphisms in Nav1.7, the first being in a patient with paroxysmal extreme pain disorder.